Johann Ludwig von Wolzogen's Philosophical and Political Thought : A Confrontation with the Ideas of Descartes and Szlichtyng, with Selected Translations - Gut, Przemysław (Brill's Studies in Intellectual History, 2026)
This volume presents the first English translations of the writings of Johann Ludwig von Wolzogen (c. 1599-1661)-theologian, philosopher, and mathematician-who emerged as one of the leading figures of the Polish Brethren, also known as the Socinians or Arians. It highlights Wolzogen's distinctive contribution to early modern European philosophy and intellectual culture, revealing the depth and originality of his engagement with the major religious and philosophical debates of his time. The accompanying introduction situates his thought within the wider currents of seventeenth-century discourse, demonstrating how the Polish Brethren-one of Europe's most innovative and reform-minded movements-anticipated key themes of modernity, including religious rationalism, toleration, and social reform.